KONTRIBUSI USAHATANI KAKAO TERHADAP PENDAPATAN RUMAH TANGGA PETANI DI DESA SINTUWU KECAMATAN PALOLO KABUPATEN SIGI - Indah, Nur; Lamusa, Arifuddin; Alamsyar, Al (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2022)
The aim of this research was to determine the income of cocoa farmers and the extent to which cocoa farming contributes to their household income in Bobo Village, Palolo Sub District, Sigi District. The study was conducted between November and December 2020, with 35 respondents chosen using a simple random sampling method from a total population of 156 cocoa farmers. Household income analysis and contribution analysis were employed for analysing data. The findings revealed that the average income of cocoa farmer respondents in Bobo Village was IDR 14,305,435.76/ha. Additionally, the cocoa farming income accounted for 25.81% of the total income of farmer households. Although the contribution of cocoa farming income was lower compared to corn farming (29.62%) and non-farming income (30.89%), it exceeded the contribution of candlenut farming income (13.68%). These results demonstrate that cocoa farming makes a substantial contribution to the overall income of the farmers.